PELATIHAN PERHITUNGAN HARGA POKOK PRODUKSI UNTUK PARA PELAKU UMKM DI KECAMATAN BATURAJA TIMUR OKU (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2022)
The purpose of this Community Service (PPM) activity is to provide an introduction to MSME participants about the concept of production costs by providing explanations and training on the assignment of production costs with various approaches, namely using full costing and variable costing methods. Through this training, participants are expected to be able to understand the concept of production costs so that they can be applied in calculating the cost of production costs in each business correctly and correctly so that it has an impact on the accuracy of setting the selling price and in the end will be able to get maximum profit and have a business with high competitiveness. The materials presented included cost accounting, cost of production, methods for determining the cost of production and the elements that make up production costs.